Purification of neuraminidase from Influenza virus subtype H5N1 - Simson Tarigan; Risa Indryani; Darminto .; Jagoda Ignjatovic (Jurnal Ilmu Ternak dan Veteriner, 2009)
Influenza-virus neuraminidase plays vital role in the survival of the organisms. Vaccination of animals with this glycoprotein confers immune responses so that enable it to protect the animals from incoming infection. Supplementation of conventional vaccines with this glycoprotein increases the protection and longevity of the vaccine. Purified neuraminidase can also be used to develop serological tests for differentiation of serologically positive animals due to infection or to vaccination. In this study purification of neuraminidase from influenza virus subtype H5N1 was described. Triton x-100 and Octyl β-D-glucopyranoside were used to extract and diluted the glycoprotein membrane. The enzymatic activity of the neuraminidase was assayed using a fluorochrome substrate, 4-methylumbelliferyl-a-D-N-acetyl neuraminic acid, which was found to be simple, sensitive and suitable for the purification purpose. The neuraminidase was absorbed selectively on an oxamic-acid agarose column. The purity of neuraminidase eluted from this affinity column was high. A higher purity of the neuraminidase was obtained by further separation with gel filtration on Superdex-200. The purified neuraminidase was enzymatically active and did not contain any detectable haemagglutinin, either by haemagglutination assay or by monospecific antibodies raised against H5N1 hemagglutinin.  The purified neuraminidase was recognized strongly by antibodies raised against an internal but only weakly by that against C-terminal regions of the neuraminidase protein of H5N1-influenza virus. The purified neuraminidase was in tetrameric forms but dissociated into monomeric form on reducing condition, or mostly dimeric form on non-reducing SDS-PAGE. Key Words: Neuraminidase, Influenza, H5N1, Methylumbelliferyl, Oxamic-acid